Simultaneous papillary carcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma of the thyroid; a case report. Issue 5 (May 2020) - Whitehouse, Laura LE.; Chengot, Preetha
Abstract: Primary lymphoma of the thyroid is an uncommon malignancy, whereas papillary thyroid carcinoma is the most common thyroid malignancy. Both have an association with Hashimoto's thyroiditis. We discuss a case of an 83 year old male who presented with a large neck swelling, which subsequently proved to be a primary thyroid lymphoma (extra-nodal marginal zone) with concurrent papillary thyroid carcinoma. These tumours manifested on a background of Hashimoto's thyroiditis. To date there have only been 13 other cases of joint papillary thyroid carcinoma and thyroid lymphoma within the literature. Our case report adds to this by discussing diagnosis, histopathological features and pitfalls in early detection.